Clinical, Imaging and Histopathology of Angioleiomyoma of the Buccal Cheek - Mohammad Jafarian; Fatemeh Mashhadi Abbas; Mitra Ghazizadeh Ahsaie; Homeira Saebnoori (Case Reports in Dentistry)
Angioleiomyoma is a benign neoplasia originating from vascular smooth muscle and very uncommon in the oral cavity. In this report, we present a rare case of angioleiomyoma in oral cavity in a 46-year-old female buccal cheek and discuss the clinical, histological, and immunohistochemical characteristics. As the treatment of choice is the complete excision, the lesion was excised under local anesthesia with no further complications. In addition, a brief update on other reported cases of angiomyoma in the oral cavity is further discussed.